1997
DOI: 10.1023/a:1026481521916
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Different antisera directed against mammalian and piscine pituitary hormones, as well as a battery of various conventional histochemical techniques (PAS, Alcian Blue pH 2.5, Bromophenol Blue) and lectins, were used to identify the different hormonal cell types in the pituitary of the Senegalese sole, Solea senegalensis. Prolactin and adrenocorticotrophic cells were located in the rostral pars distalis of the pituitary. Gonadotrophic, thyrotrophic and growth hormone cells were distributed in the proximal pars d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 35 publications
3
1
0
Order By: Relevance
“…GH cells were located mainly in the dorsal central PD and were arranged in thin strands in the ventral part of A. gigas pituitary gland. This distribution is in agreement with other teleosts, as reported previously (see Ball and Baker 1969;Holmes and Ball 1974;Schreibman et al 1973) and in more recent studies (Parhar et al 1998;Rendón et al 1997;Rodríguez-Gómez et al 2001;Sánchez Cala et al 2003;Segura-Noguera et al 2000;Vissio et al 1997), although some variations may occur, depending on the species and developmental stage (García-Hernández et al 1996;Villaplana et al 2000;Sánchez Cala et al 2003).…”
Section: Structure Of the Pituitary Glandsupporting
confidence: 93%
See 1 more Smart Citation
“…GH cells were located mainly in the dorsal central PD and were arranged in thin strands in the ventral part of A. gigas pituitary gland. This distribution is in agreement with other teleosts, as reported previously (see Ball and Baker 1969;Holmes and Ball 1974;Schreibman et al 1973) and in more recent studies (Parhar et al 1998;Rendón et al 1997;Rodríguez-Gómez et al 2001;Sánchez Cala et al 2003;Segura-Noguera et al 2000;Vissio et al 1997), although some variations may occur, depending on the species and developmental stage (García-Hernández et al 1996;Villaplana et al 2000;Sánchez Cala et al 2003).…”
Section: Structure Of the Pituitary Glandsupporting
confidence: 93%
“…The ACTH/MSH family The ACTH amino acid sequence at position 1-24 (of 39 amino acid residues that composes the entire molecule) seems to be constant in mammals (Agulleiro et al 2006) and in teleosts, as most of the studied species have cells immunoreactive to human ACTH (1-24) antiserum Grandi et al 2003;Laiz-Carión et al 2003;Rendón et al 1997;Sánchez Cala et al 2003;Segura-Noguera et al 2000). In our study, this antiserum also immunostained ACTH cells at the rostral part of the pituitary.…”
Section: Structure Of the Pituitary Glandmentioning
confidence: 99%
“…These results are consistent with morphological studies in sole and other teleosts, which showed the presence of Gnrh-ir cells and/or fibers in the terminal nerve area, known for the presence of Gnrh-3 cells (Rend on et al 1997;Gonz alez-Martínez et al, 2002), and in the proximal pars distalis of the pituitary in the vicinity of gonadotropic cells (Rend on et al 1997). Similar results were obtained in goldfish, where Gnih-3 treatment reduced gnrh-3 transcript levels at 12 hr postinjection (Qi et al, 2013a).…”
Section: Abundant Studies Have Reported the Inhibitory Role Of Gnih Onsupporting
confidence: 91%
“…This is the typical distribution for MSH and SL cells reported for other teleosts [6,8,[20][21][22]. However, in Solea senegalensis [46] and Thalassoma duperry [31] MSH cells appear to surround the SL cells.…”
Section: Acth and α-Msh Cellssupporting
confidence: 71%